Relationship between HER2 and JAK/STAT-SOCS3 signaling pathway and clinicopathological features and prognosis of ovarian cancer. Issue 5 (4th May 2017) - Shang, An-Quan; Wu, Jian; Bi, Feng; Zhang, Yu-Jie; Xu, Lei-Rong; Li, Ling-Ling; Chen, Fei-Fei; Wang, Wei-Wei; Zhu, Jian-Jun; Liu, You-Yi
ABSTRACT: Objective: The study aims to explore the relationship between expressions of HER2 and JAK/STAT3-SOCS3 signaling pathway and clinicopathological features and prognosis of ovarian cancer (OC).Methods: A total of 136 OC patients were collected. Immunohistochemistry was applied to measure the expressions of STAT3, p-STAT3, SOCS3, HER2 and p-HER2 in the tumor tissues and adjacent normal tissues. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the mRNA expressions of HER2, SOCS3 and STAT3 and western blotting was applied for protein expressions of HER2, p-HER2, SOCS3, STAT3 and p-STAT3 in the tumor tissues and adjacent normal tissues. Flow cytometry was used for the cell apoptosis in the blank, afatinib (A), ruxolitinib (R) and afatinib + ruxolitinib (A + R) groups. Follow-up was performed to explore relationship of HER2, SOCS3, and STAT3 expressions with survival time of OC patients.Results: HER2, p-HER2, STAT3, and p-STAT3 expressions were higher while SOCS3 expression was lower in the tumor tissues. The positive expressions of STAT3, HER2, p-HER2 and p-STAT3 were lower while the positive expression of SOCS3 was higher in the adjacent normal tissues. The expressions of HER2, SOCS3, and p-STAT3 were associated with clinical stage and lymph node metastasis (LNM), and STAT3 expression has correlation with histological grade and LNM. The mRNA and protein expressions of HER2, STAT3 and p-STAT3 in the tumor tissues were higher than those in the adjacent normal tissues, but SOCS3 expression was significantly decreased. The positive expressions of HER2, p-HER2 and STAT3, the negative expression of SOCS3 and pathological stages were important risk factors for the prognosis of patients with OC.Conclusion: Our study showed that the expressions of HER2, STAT3, and SOCS3 are associated with the progression of OC, and higher expressions of HER2 and STAT3 and lower expression of SOCS3 predict poor prognosis of OC.